Mechanical properties of polypropylene/clay nanocomposites: Effect of clay content, polymer/clay compatibility, and processing conditions - Tarapow, J. A. (2009)
In this work, polypropylene/clay nanocomposites with 0.5, 1, 3, and 5 wt % of montmorillonite (MMT) (unmodified clay) were prepared by intensive mixing at 50 rpm and 10 min of mixing. For the highest clay content (5 wt %), the initial materials or the processing conditions were changed to study their independent effect. On one hand, 10 wt % of PP‐graft‐MA (PP‐g‐MA) was incorporated or MMT was replaced by organomodified clays (C10A and C30B). On the other side, for the initial system, the speed of rotation (100 and 150 rpm) and the mixing time (5 and 15 min) were altered. In all cases, the state of the clay inside the matrix (DRX), the degree of dispersion in the micro (SEM) and nano (TEM) scales, and the rheological and mechanical properties were analyzed. It was found that the stiffness increased with clay content, whereas tensile and impact strength did not significantly change. Although intercalated structures were observed in the composites with unmodified clay, in the composites with modified clay or PP‐g‐MA, improved dispersion of clay in PP was found. The mechanical properties increased accordingly. The degree of dispersion of the filler in the matrix appeared to be unaffected by the changes in the processing conditions introduced. Finally, the elastic modulus was modeled by using an effective filler‐parameter model based on Halpin–Tsai equations, which also allowed estimating the relative degree of dispersion.